Strategi produksi bunyi vokal oleh ventrilokuis Indonesia - Kustiawan, Roni; Indrayani, Lia Maulia; Ratnasari, Dewi (Universitas Mulawarman, 2023)
Ventriloquism or voice magic illusion involves the ability of speakers to control lip and jaw movements to create the impression that sound or speech comes from a puppet being played. This study aims to analyze the strategies used by ventriloquists in producing vowel sounds in Indonesian using the acoustic analysis method (spectrography). Our research data was obtained from three Indonesian ventriloquists who appeared in a video entitled